2008
DOI: 10.1111/j.1365-313x.2008.03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Two short‐chain dehydrogenase/reductases, NON‐YELLOW COLORING 1 and NYC1‐LIKE, are required for chlorophyll b and light‐harvesting complex II degradation during senescence in rice

Abstract: SummaryYellowing, which is related to the degradation of chlorophyll and chlorophyll-protein complexes, is a notable phenomenon during leaf senescence. NON-YELLOW COLORING1 (NYC1) in rice encodes a membrane-localized short-chain dehydrogenase/reductase (SDR) that is thought to represent a chlorophyll b reductase necessary for catalyzing the first step of chlorophyll b degradation. Analysis of the nyc1 mutant, which shows the staygreen phenotype, revealed that chlorophyll b degradation is required for the degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
260
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(270 citation statements)
references
References 40 publications
1
260
2
7
Order By: Relevance
“…It was suggested that decreasing the chlorophyll b portion in the chlorophyll-protein complexes of the photosystems causes their destabilization (Horn and Paulsen, 2004) and could trigger both apoprotein and chlorophyll degradation (Rü diger, 2002;Hö rtensteiner, 2006). This was corroborated recently by cloning of NON-YELLOW COLORING1 (NYC1) and NYC1-LIKE (NOL) Sato et al, 2009). NYC1 and NOL encode two subunits of chlorophyll b reductase (Sato et al, 2009), which catalyzes the first half of chlorophyll b to chlorophyll a reduction, i.e., conversion of chlorophyll b to 7-hydoxymethyl chlorophyll a. nyc1 and nol mutants stay green during senescence and thereby selectively retain photosystem II (PSII) light-harvesting complex subunits (LHCII) and exhibit particularly high concentrations of chlorophyll b.…”
Section: Introductionmentioning
confidence: 57%
“…It was suggested that decreasing the chlorophyll b portion in the chlorophyll-protein complexes of the photosystems causes their destabilization (Horn and Paulsen, 2004) and could trigger both apoprotein and chlorophyll degradation (Rü diger, 2002;Hö rtensteiner, 2006). This was corroborated recently by cloning of NON-YELLOW COLORING1 (NYC1) and NYC1-LIKE (NOL) Sato et al, 2009). NYC1 and NOL encode two subunits of chlorophyll b reductase (Sato et al, 2009), which catalyzes the first half of chlorophyll b to chlorophyll a reduction, i.e., conversion of chlorophyll b to 7-hydoxymethyl chlorophyll a. nyc1 and nol mutants stay green during senescence and thereby selectively retain photosystem II (PSII) light-harvesting complex subunits (LHCII) and exhibit particularly high concentrations of chlorophyll b.…”
Section: Introductionmentioning
confidence: 57%
“…Although the phenotypes of CBR-deficient mutants during senescence have been studied (Kusaba et al 2007;Horie et al 2009;Sato et al 2009), the effect of the light conditions on the degradation activity of chlorophyll b has not yet been determined. In this report, we analyzed mutant plants that are defective in chlorophyll b degradation under a high-light treatment to elucidate the role of chlorophyll b degradation in the regulation of the light-harvesting system.…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that it is involved with the chlorophyll catabolic pathway, the absence of known domains has made it difficult to deduce a function from the gene sequence (Aubry et al 2008;Sato et al 2009). …”
Section: Cotyledon Colormentioning
confidence: 99%